Antagonistic regulation of apoptosis and differentiation by the cut transcription factor represents a tumor-suppressing mechanism in Drosophila. - Zhai, Z.; Ha, N.; Papagiannouli, F.; Hamacher-Brady, A.; Brady, N.; Sorge, S.; Bezdan, D.; Lohmann, I. (PLoS Genetics, 2012)
Apoptosis is essential to prevent oncogenic transformation by triggering self-destruction of harmful cells, including those unable to differentiate. However, the mechanisms linking impaired cell differentiation and apoptosis during development and disease are not well understood. Here we report that the Drosophila transcription factor Cut coordinately controls differentiation and repression of apoptosis via direct regulation of the pro-apoptotic gene reaper. We also demonstrate that this regulatory circuit acts in diverse cell lineages to remove uncommitted precursor cells in status nascendi and thereby interferes with their potential to develop into cancer cells. Consistent with the role of Cut homologues in controlling cell death in vertebrates, we find repression of apoptosis regulators by Cux1 in human cancer cells. Finally, we present evidence that suggests that other lineage-restricted specification factors employ a similar mechanism to put the brakes on the oncogenic process.